2017
DOI: 10.18632/oncotarget.15984
|View full text |Cite
|
Sign up to set email alerts
|

IL-33-induced alternatively activated macrophage attenuates the development of TNBS-induced colitis

Abstract: Accumulated data have shown that alternatively activated macrophage exerts a modulatory role in many diseases, including colitis. Interleukin-33 (IL-33), a critical modulator in adaptive and innate immune, has been implicated in autoimmunity and inflammation. Previously, we have reported that IL-33 functions as a protective modulator in TNBS-induced colitis, which is closely related to a Th1-to-Th2/Treg switch. Here, we present novel evidence suggesting that IL-33 primes macrophage into alternatively activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
(49 reference statements)
1
32
0
Order By: Relevance
“…In other studies, IL-33 was protective in colitis by inducing polarization of macrophages to M2 macrophages, which are typically associated with T H 2 cytokines and promote resolution of inflammation [131, 132]. In one study, these M2 macrophages, which they termed alternatively activated macrophages, were isolated from IL-33-treated mice and transferred to mice with TNBS-induced colitis [131].…”
Section: Il-33/st2 Signaling Axis In Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, IL-33 was protective in colitis by inducing polarization of macrophages to M2 macrophages, which are typically associated with T H 2 cytokines and promote resolution of inflammation [131, 132]. In one study, these M2 macrophages, which they termed alternatively activated macrophages, were isolated from IL-33-treated mice and transferred to mice with TNBS-induced colitis [131].…”
Section: Il-33/st2 Signaling Axis In Inflammatory Bowel Diseasementioning
confidence: 99%
“…In one study, these M2 macrophages, which they termed alternatively activated macrophages, were isolated from IL-33-treated mice and transferred to mice with TNBS-induced colitis [131]. This conferred protection to recipient mice, in which there was a significant decrease in intestinal disease and inflammatory markers [131].…”
Section: Il-33/st2 Signaling Axis In Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 preferentially activates type 2 immune responses; it promotes M2 macrophage polarization, activates ILC2s and Th2 cells [20,21], and functions as a disease-sensitizing mediator in the pathogenesis of allergic disorders, including respiratory allergies (asthma and allergic rhinitis) and skin allergies (atopic dermatitis) [2]. …”
Section: Il-33 and St2 Signallingmentioning
confidence: 99%
“…In mouse models of experimental colitis induced by dextran sulphate sodium (DSS) or trinitrobenzene sulfonic acid (TNBS), deficiency of the IL33 or IL1RL1 genes leads to amelioration of the disease, compared to its outcome in wild-type control mice, and treatment with an ST2 blocking antibody ameliorates experimental colitis by enhancing mucosal healing in mice [58]. However, other studies have shown that administration of recombinant IL-33 ameliorates TNBS-induced inflammatory bowel disease (IBD) in mice [20,59]. Intriguingly, treatment with IL-33 at the onset of DSS-induced colitis exacerbates the disease severity, whereas treatment with IL-33 during the recovery phases ameliorates DSS-induced colitis.…”
Section: Gastrointestinal Diseasesmentioning
confidence: 99%